Cryptocurrencies and traditional financial instruments: a comparative analysis and perspectives - Shevchenko, Maryna Mykolaivna; Havryliuk, V.; Rudych, O. (Чорноморський державний університет ім. Петра Могили, 2023)
Over the past few years, cryptocurrencies have become popular and are being used just as actively as traditional financial instruments. What is specific about cryptocurrencies is that they are only digital assets, but they can be used for storing and transferring significant sums of money (with low fees and no intermediaries), as well as for converting into fiat money. Despite the popularity of cryptocurrencies, traditional financial instruments remain the basis of the global economy due to their regulation. The advantages and disadvantages inherent in traditional financial instruments and cryptocurrencies shape the prospects for the development of each of these systems, taking into account that each user has their own considerations regarding the acceptability of profitability and riskiness of operations. The study aims to provide opportunities for comparative analysis of cryptocurrency and traditional financial instruments and to determine their development prospects. The results of the study demonstrate that the use of cryptocurrencies for transactions, combined with their advantages such as decentralization, anonymity, and fast transaction processing (compared to banking transactions), increases transaction profitability while also offering relative security and stability against external factors. However, the disadvantages of cryptocurrency, including high volatility, low liquidity, lack of regulation and limited circulation, risk of losing access keys and technical problems, and potential use for illegal transactions, collectively increase the complexity and risk of transactions with them. Regarding the use of traditional financial instruments, their advantages, such as safety and convenience, are increased when used in combination with other instruments (including smart investments, ease of use, easy understanding and accessibility for different categories of people, reliability, and a wide range of types and instruments). However, they are also limited by certain disadvantages that decrease the profitability of transactions with them (such as high commissions, low returns on some instruments, and risk of inflation). The study indicates prospects for the joint development of traditional financial instruments and cryptocurrencies, including the inclusion of cryptocurrencies in the financial services of traditional financial institutions, adaptation of electronic payment systems for cryptocurrencies to reduce transaction costs and increase their efficiency, and creation of hybrid new financial instruments that can be more efficient and convenient for users. За останні кілька років криптовалюти стали популярними та використовуються так само ак- тивно, як і традиційні фінансові інструменти. Специфічним є те, що криптовалюти є лише циф- ровими активами, однак вони можуть бути використані для зберігання і переказування значних сум (з низькою комісією та без посередників), а також для конвертації у фіатні гроші. Незважа- ючи на популярність криптовалюти, традиційні фінансові інструменти залишаються основою для світової економіки через їх регульованість. Саме недоліки та переваги, властиві традицій- ним фінансовим інструментам та криптовалютам, формують перспективи для розвитку кожної з цих систем, зважаючи на те, що кожен їх користувач має власні міркування щодо прийнят- ності доходності та ризикованості операцій. Дослідження спрямоване на забезпечення мож- ливостей для порівняльного аналізу криптовалют і традиційних фінансових інструментів та виз- начення перспектив їх розвитку. За результатами дослідження було доведено, що використання криптовалют для операцій, їх переваги у сукупності підвищують доходність операцій за рахунок децентралізації, анонімності та можливості швидкого виконання операцій (у порівнянні з банківськими транзакціями), а також відносної безпеки операцій та їх стійкості до зовнішніх чинників. У той же час недоліки криптовалюти (зокрема, її висока волатильність, низька ліквідність, брак регулювання та обмежений обіг, ризик втрати ключів доступу та виникнення технічних проблем, можливість використання для нелегальних операцій) у сукупності підвищують ризикованість та складність операцій з нею. Щодо використання традиційних фінансових інструментів, їх переваги у сукупності підвищують безпеку та зручність операцій з ними, хоча їм властиві недоліки, які обмежують доходність операцій з такими інструментами. За результатами дослідження виявлені перспективи спільного розвитку традиційних фінансових інструментів та криптовалют, зокрема: включення криптовалют до фінансових послуг традиційних фінансових установ; адаптації електронних платіжних систем криптовалют для зниження витрат на транзакції та підвищення їх ефективності; створення гібридних нових фінансових інструментів, які можуть бути більш ефективними та зручними для користувачів.
Криптовалюти і традиційні фінансові інструменти: порівняльний аналіз і перспективи
Keywords: transaction security; digital assets; transactions; credit products; funds; bank deposits; безпека трансакцій; цифрові активи; трансакції; кредитні продукти; фонди; банківські депозити